RANCANG BANGUN APLIKASI SISTEM PENJADWALAN KULIAH DAN KEHADIRAN DOSEN MENGAJAR BERBASIS ANDROID MENGGUNAKAN REST SERVER - M Anton Permana (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
The lecture scheduling system and the presence of teaching lecturers on the "XYZ" campus have been carried out manually so that it often interferes with the effectiveness of the lecturer and student learning process. This prompted the writer to design and build an application for lecturing scheduling systems and the presence of Android-based teaching lecturers using Rest Server technology. The method used in designing this application is Unified Process (UP) while its implementation uses the Firemonkey Framework. This system is expected to overcome problems that often arise in the manual scheduling system for lectures on the "XYZ" campus.